Митний пост-аудит як інструмент пришвидшення міжнародного товарообігу та переходу до якісно нової концепції партнерських відносин “митниця – суб’єкти ЗЕД” - Фальковський, А. О.; Єршов, Д. А.; Falkovskyi, Andrii; Yershov, Denys (Одеса : Гельветика, 2019)
Статтю присвячено дослідженню правових основ митного пост-аудиту, стан його розвитку та проблемні питання у вітчизняному правовому полі, що знижують його ефективність. Запропоновано якісно новий підхід до розуміння суті даного явища у світлі партнерських відносин “митниця-суб’єкти ЗЕД”. The article is devoted to the research of the legal bases of customs post-audit, the state of its development position and the problematic issues in the domestic legal field that reduce its effectiveness. Customs control in developed democratic countries is one of the main forms of customs control applied by the customs authorities in the course of customs control. The essence of this phenomenon is that the basic customs procedures, which according to the legislation of the respective country must be carried out for goods moving across the border (import, export), are not applicable at the point of entry at the direct movement of goods or at the customs office of destination / departure, but upon completion of customs clearance and release for free circulation. Appropriate activity allows to conduct financial analysis of the company on the basis of accounting and tax reporting, and to obtain the most informative indicators that will give an objective and accurate picture of the financial condition of the organization, its profits and losses, changes in the structure of assets and liabilities, in the accounts with debtors and creditors on the basis of which it is possible to evaluate the ability of an organization to function continuously and fulfill its obligations regarding customs payments, ransom and penalties. The article identifies and structures the main problematic issues that hamper the functioning of the customs post-audit in Ukraine. On the basis of the analysis of international legislation on customs issues, it is determined that the relevant institute is an integral part of the customs system not only of Ukraine, but of other countries as well, in the context of globalization, and in particular of Eurointegration processes. A breakthrough new approach to understanding the essence of this phenomenon in the light of new concept of partnership relations “customs – company engaged in foreign trade” is proposed. A conceptually new paradigm of understanding of this institute has been proposed and substantiated, what allows, with available or even smaller resources, to achieve better results in the work and to ensure the fulfillment of the tasks assigned to the customs service.
Фальковський А. О., Єршов Д. А. Митний пост-аудит як інструмент пришвидшення міжнародного товарообігу та переходу до якісно нової концепції партнерських відносин “митниця – суб’єкти ЗЕД” / А. О. Фальковський, Д. А. Єршов // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". - Одеса : Видавничий дім «Гельветика», 2019. - № 4. – C. 73-89.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; таможенный контроль; таможенный пост-аудит; правовые основы таможенного пост-аудита; внешнеэкономическая деятельность; митний контроль; митний пост-аудит; зовнішньоекономічна діяльність; правові засади митного пост-аудиту; customs control; customs post-audit; legal bases of customs post-audit